Abraham Firkovitsh och hans samlingar i Rossijskaja Nacional'naa ja Biblioteka i S:t Petersburg - Harviainen, Tapani (Nordisk judaistik/Scandinavian Jewish Studies, 1993)
Abraham ben Shemuel Firkovitsh (1787–1874) is one of the most influential collectors of manuscripts and antiquities known in the history of orientalism. He was born in Ukraine and was of Karaite origin. He pursued studies in Hebrew language and literature. On his agenda was to show that the Karaites had deep roots in Russia, but that they should not follow the same restrictions as the Jews in the country. His personal archive is today found at the Russian national library in St. Petersburg. In the archive there are more than a thousand letters written by Firkovitsh during his travels.